PRAGMATIC FEATURES OF DEIXIS IN THE WORKS OF ULUGHBEK HAMDAM (TAMADDUN NURI JURNALI, 2025)
This article studies the pragmatic aspects of deixis in modern Uzbek prose. The main types of deixis in linguistics - person, place, time, discourse and social deixis - are analyzed using the works of the writer Ulugbek Hamdam as an example, and their role in the work of art is highlighted. Also, the analysis of the examples considers the communicative functions of deixis units, namely, the identification of speech participants, reference to time, emotional assessment of the person and their role in the formation of the context.